2007
DOI: 10.1097/01.gme.0000243571.55699.4a
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of citalopram on climacteric symptoms

Abstract: Citalopram is an effective alternative treatment option for patients who do not want to take HT for the alleviation of climacteric symptoms. Adjuvant treatment with a selective serotonin reuptake inhibitor increases the effectiveness of HT for the treatment of climacteric symptoms in women who had responded inadequately to HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
1
32
0
4
Order By: Relevance
“…We also extracted hot flashes/vasomotor symptoms assessed by scores (e.g., hot flash score, 10 vasomotor score, 11 modified Kupperman index, 20 Rand mood score, 21 hot flashrelated daily interference scale 22 and menopausal rating score 23 ) whenever available and from those studies that did not report daily hot flash frequency.…”
Section: Summary Of Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We also extracted hot flashes/vasomotor symptoms assessed by scores (e.g., hot flash score, 10 vasomotor score, 11 modified Kupperman index, 20 Rand mood score, 21 hot flashrelated daily interference scale 22 and menopausal rating score 23 ) whenever available and from those studies that did not report daily hot flash frequency.…”
Section: Summary Of Measuresmentioning
confidence: 99%
“…Nevertheless, studies of SSRIs have demonstrated mixed results; some studies demonstrated benefit by reducing hot flashes by 50-60 % while others reported no effect. [9][10][11] Therefore, we conducted a systematic review to synthesize and summarize the best available evidence on the use of SSRIs to treat hot flashes in healthy menopausal women. The aim of this comparative effectiveness review is to evaluate the efficacy and side effect profile to aid in decision making.…”
Section: Introductionmentioning
confidence: 99%
“…This study also recommended citalopram as a treatment for hot flashes [19]. Another research compared the separate impacts of citalopram and venlafaxine on hot flashes, and found citalopram to be more effective in this respect [20]. The study on hot flashes due to niacin intake proved that aspirin taken with niacin would decrease hot flashes and general body temperature [25].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the significant difference observed for the simultaneous effects of these two drugs on hot flashes, it could be concluded that the efficacy of citalopram plus aspirin is higher than citalopram alone. Other studies had previously established the separate positive effects of citalopram and aspirin on reducing hot flashes [18][19][20][21][22]. Therefore, if these drugs could separately alleviate hot flashes, their simultaneous use was expected to leave a higher impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation